Hydrogen peroxide formation in the interaction of oxygen with boron-containing Pd catalysts prereduced by hydrazine in aqueous acidic medium containing bromide anions - Choudhary, Vasant R.; Samanta, C. (Catalysis Letters, 2005)
Interaction of molecular oxygen with Pd/BPO4 or ZrO2 (or Al2O3, CeO2, TiO2) - B2O3 catalysts, prereduced by hydrazine hydrate, in an aqueous acidic (H2SO4 or H3PO4) reaction medium containing bromide ions leads to the formation of H2O2. However, in the absence of boron in the catalyst and also in the absence of acid and/or bromide ions in the reaction medium, almost no H2O2 is formed.
Keywords: boron-containing Pd catalysts; Hydrogen peroxide; oxygen-catalyst interactions

Novel route for in-situ H2O2 generation from selective reduction of O-2 by hydrazine using heterogeneous Pd catalyst in an aqueous medium - Choudhary, Vasant R.; Samanta, C.; Jana, Prabhas (Chemical Communications, 2005)
Hydrogen peroxide in high yields can be generated with high efficiency at mild conditions (25 degrees C and atmospheric pressure) with the formation of only environment-friendly by-products (N-2 and H2O) by a reduction of O-2 by hydrazine from its hydrate/salt with its complete conversion in a short reaction period (<= 0.5 h) using a easily separable supported Pd catalyst (Pd/Al2O3, Pd/Ga2O3 or Pd/C) in an acidic aqueous medium in the presence of bromide anions; the presence of both acid (protons) and bromide anions is essential for the selective reduction of O-2 by hydrazine to H2O2 and in their absence, the reaction leads only to the formation of water.

Direct oxidation of H-2 to H2O2 over Pd-based catalysts: influence of oxidation state, support and metal additives - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
The influence of oxidation state (reduced and oxidized), support (ZrO2, Ga2O3, CeO2, SiO2, H-beta, ThO2, CeO2-ZrO2, BPO4 and Pd/Al2O3) and precious metal additives (Au, Pt, Rh and Ru) on the direct H2O2 synthesis has been investigated over Pd-based catalysts. For all the supports investigated herein, the oxidized Pd catalysts showed significantly superior H2O2 yields as compared to their reduced counterparts. The effect of the Pd oxidation state was found to be more important for determining the H2O2 yields than the particle size and surface area properties of the catalyst system. An excellent correlation was observed between the H2O2 selectivity and H2O2 decomposition activity of the oxidized Pd catalysts. The oxidized Pd catalysts showed almost an order of magnitude lower H2O2 decomposition activity than the reduced catalysts. The H2O2 yield in the H-2 to H2O2 oxidation passed through a maximum with increase in the An concentration. Although a similar effect was also observed in case of Pt, Au was found to be a superior promoter for the direct H2O2 synthesis process. Addition of Rh and Ru was found to be detrimental for the H2O2 yields; these results can be explained in terms of increased H2O2 decomposition activity and/or enhanced H-2 to H2O reaction activity in their presence. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: decomposition; direct synthesis; H2O2; metal additives; oxidation state; Pd catalysts; supports

Factors influencing decomposition of H2O2 over supported Pd catalyst in aqueous medium - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Journal of Molecular Catalysis A-Chemical, 2006)
Since H2O2 decomposition can result in selectivity/yield loss in the direct H2O2 synthesis process from H-2 and O-2 over supported Pd catalysts, it is important to have an enhanced understanding about the factors affecting the H2O2 decomposition reaction. Herein, detailed studies have been undertaken to investigate the influence of different factors, such as (a) nature and concentration of acid in reaction medium, (b) nature and concentration of halide in presence and absence of acid in reaction medium, (c) pretreatment procedures and (d) catalyst modification by incorporation of different halides, on the H2O2 decomposition reaction over a 5% Pd/C catalyst in aqueous medium at 25 degrees C. This study has shown that the H2O2 decomposition activity is profoundly influenced by all the above factors. The effectiveness of the acids in suppressing the H2O2 decomposition activity decreased in the following order: hydroiodic acid > hydrobromic acid > hydrochloric acid >> acetic acid > phosphoric acid > sulfuric acid > perchloric acid. The ability of the acid to decrease the H2O2 decomposition activity was found to very strongly depend on the nature of its associated anion. Halides, such as iodide, bromide and chloride were particularly effective in suppressing the H2O2 decomposition activity. Oxidation pretreatment of the catalyst was found to strongly suppress its H2O2 decomposition activity, while a reduction treatment was found to promote its activity. A gradual decrease in the H2O2 decomposition activity of the catalyst was observed with each successive usage due to in situ sub-surface oxidation of Pd by H2O2. Halide incorporation either via the reaction medium or prior catalyst modification had a similar qualitative effect on the H2O2 decomposition activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acid; H2O2 decomposition; H2O2 synthesis; halides; Pd catalysts; pretreatment